Recent Progress in Recombinant Influenza Vaccine Development Toward Heterosubtypic Immune Response - Carascal, Mark B.; Pavon, Rance Derrick N.; Rivera, Windell L. (Frontiers in Immunology, 2022)
Flu, a viral infection caused by the influenza virus, is still a global public health concern with potential to cause seasonal epidemics and pandemics. Vaccination is considered the most effective protective strategy against the infection. However, given the high plasticity of the virus and the suboptimal immunogenicity of existing influenza vaccines, scientists are moving toward the development of universal vaccines. An important property of universal vaccines is their ability to induce heterosubtypic immunity, i.e., a wide immune response coverage toward different influenza subtypes. With the increasing number of studies and mounting evidence on the safety and efficacy of recombinant influenza vaccines (RIVs), they have been proposed as promising platforms for the development of universal vaccines. This review highlights the current progress and advances in the development of RIVs in the context of heterosubtypic immunity induction toward universal vaccine production. In particular, this review discussed existing knowledge on influenza and vaccine development, current hemagglutinin-based RIVs in the market and in the pipeline, other potential vaccine targets for RIVs (neuraminidase, matrix 1 and 2, nucleoprotein, polymerase acidic, and basic 1 and 2 antigens), and deantigenization process. This review also provided discussion points and future perspectives in looking at RIVs as potential universal vaccine candidates for influenza.